Low Intensity Exercise Training Improves Skeletal Muscle Regeneration Potential - Pietrangelo, Tiziana; Di Filippo, Ester S.; Mancinelli, Rosa; Doria, Christian; Rotini, Alessio; Fanò-Illic, Giorgio; Fulle, Stefania (Frontiers in Physiology, 2015)
Purpose: The aim of this study was to determine whether 12 days of low-to-moderate exercise training at low altitude (598 m a.s.l.) improves skeletal muscle regeneration in sedentary adult women. Methods: Satellite cells were obtained from the vastus lateralis skeletal muscle of seven women before and after this exercise training at low altitude. They were investigated for differentiation aspects, superoxide anion production, antioxidant enzymes, mitochondrial potential variation after a depolarizing insult, intracellular Ca2+ concentrations, and micro (mi)RNA expression (miR-1, miR-133, miR-206). Results: In these myogenic populations of adult stem cells, those obtained after exercise training, showed increased Fusion Index and intracellular Ca2+ concentrations. This exercise training also generally reduced superoxide anion production in cells (by 12% to 67%), although not in two women, where there was an increase of ~15% along with a reduced superoxide dismutase activity. miRNA expression showed an exercise-induced epigenetic transcription profile that was specific according to the reduced or increased superoxide anion production of the cells. Conclusions: The present study shows that low-to-moderate exercise training at low altitude improves the regenerative capacity of skeletal muscle in adult women. The differentiation of cells was favored by increased intracellular calcium concentration and increased the fusion index. This low-to-moderate training at low altitude also depicted the epigenetic signature of cells.